Ketika Timeline Mengalahkan Deadline: Pengaruh Adiksi Media Sosial terhadap Prokrastinasi Akademik - Dea Puri Tasripah; Nita Rohayati; Devi Marganing Tyas (Universitas Muhammadiyah Metro, 2025)
Academic procrastination refers to the intentional delay in initiating or completing academic tasks despite awareness of potential negative consequences. This behavior has become increasingly prevalent among university students, particularly in the context of intensive social media use. This study aimed to examine the effect of social media addiction on academic procrastination among students at private universities in Karawang. A quantitative approach with a causal research design was employed. The participants consisted of 366 undergraduate students selected using a non-probability quota sampling technique. Data were collected using the Academic Procrastination Scale developed by McCloskey and Scielzo and the Bergen Social Media Addiction Scale adapted into Indonesian. Data analysis was conducted using simple linear regression with the assistance of SPSS. The results indicated that social media addiction had a positive and significant effect on academic procrastination, as evidenced by a significance value of 0.000 (p < 0.05). The coefficient of determination (RÂ²) showed that social media addiction contributed 20.2% to the variance in academic procrastination, while the remaining 79.8% was influenced by other factors not examined in this study. These findings suggest that higher levels of social media addiction are associated with a greater tendency for students to delay academic tasks. Although the magnitude of the effect is relatively modest, the results highlight social media addiction as an important contributing factor to academic procrastination. This study underscores the need for increased awareness among students regarding the impact of excessive social media use on academic behavior and time management. The findings also provide practical implications for universities in developing preventive programs, such as time-management training and counseling services, to reduce academic procrastination associated with problematic social media use.